The COVID 19 Pandemic Lessons in the Area of Security, Social Policy and Culture: The Case with Bulgaria: Array - Popova, Juliana; Koev, Krasimir; Popova, Ana (Journal of Danubian Studies and Research, 2021)
Objectives: The aim of this paper is to discuss from an interdisciplinary perspective some lessons learnt from the global COVID 19 pandemic in the area of security, social policy and culture. Prior Work: Theoretical and experimental research of the authors in these three fields. Approach: Overview and analysis of the data collected by the authors with the application of two methods - focus group and method of critical incidents. Results: The empirical results identify the respondents’ perceptions and attitudes towards a number of issues like: human safety, societal and social security, culturally specific reactions and behaviour, etc. Implications: The paper can stimulate a larger discussion in the scientific circles about the necessity of joint research on different aspects of COVID 19 pandemic and its reflections. Value: The study will contribute to positioning the global pandemic and its various dimensions as one of the most topical issues in the contemporary interdisciplinary research.